Monogeneans of the malabar grouper Epinephelus malabaricus (Perciformes, Serranidae) off New Caledonia, with a description of six new species of Pseudorhabdosynochus (Monogenea: Diplectanidae) - Justine, Jean-Lou; Sigura, Aude (Zootaxa, 2007)
Eleven species were differentiated among more than 300 monogeneans collected on the gills of two wild malabar groupers, Epinephelus malabaricus, caught in the lagoon of New Caledonia, South Pacific. Diplectanids included seven species of Pseudorhabdosynochus Yamaguti, 1958, which were differentiated mainly on the basis of morphology of the sclerotised vagina. P. manifestus n. sp. was the most abundant species (65–80% of the diplectanids); all other species were rare. It is characterised by morphology of its vagina, in general shape of a question mark. P. malabaricus n. sp. and P. maternus n. sp. both have a vagina with two spherical chambers, and are differentiated on the basis of measurements of these chambers. P. manipulus n. sp. has an elongate vagina with a long primary chamber. P. marcellus n. sp. has a long vagina with two bends. P. maaensis n. sp. has a long vagina with a straight primary canal and the two chambers united in a common sclerotised part. Two specimens were provisorily attributed to P. cf. shenzhenensis Yang, Zeng & Gibson, 2005. Diplectanum maa n. sp. has a funnel-shaped male copulatory organ. Two species of Haliotrema (Ancyrocephal-idae) and Pseudomegalocotyla sp. (Capsalidae) are mentioned but not described. The presence of 11 species of monogeneans in this fish, after a previous published record of 12 species in E. maculatus, provides additional argument for existence of a very rich fauna of monogeneans in groupers, and an impressive parasite biodiversity in coral reef fish in general. Lists are given for other parasites of the malabar grouper, including monogeneans, digeneans, cestodes and nematodes, including new records from New Caledonia; more than 40 parasite species have been recorded in the literature. The malabar grouper is a major fish for aquaculture in South East Asia and a precise description of its parasites is needed for identification of potential threats to farmed fish.